Can Artificial Intelligence Finally Solve the Medication Adherence Crisis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Medication non-adherence—the failure to take medicines as prescribed—is a global public health crisis. It is estimated to contribute to approximately 125,000...
Keywords: Digital Health; Artificial Intelligence; Medical Ethics; Patient Care; Machine Learning